PENGARUH DANA DESA TERHADAP TINGKAT KEMISKINAN DAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN/KOTA PROVINSI BALI - Kalpika Sunu, Made Krisna; Suyana Utama, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study was to analyze the effect of village funds on the level of poverty and the welfare of the community in the regency / city of the Province of Bali. Village fund data was obtained from the Bali Province Community and Village Empowerment Service, while the poverty rate and Human Development Index were obtained from the Central Statistics Agency of Bali Province in 2015-2017. The data analysis technique used in this study is descriptive statistics and path analysis. The results of this study indicate that village funds have a negative and significant effect on poverty levels. This means that the higher the village fund, the lower the poverty rate. Village funds have a positive and significant effect on people's welfare. This means that the higher the village funds, the higher the welfare of the community in the area. The poverty level has a negative and significant effect on people's welfare, meaning that the higher the poverty level, the lower the welfare of the community